Functional mimetic of the G-protein coupled receptor CXCR4 on a soluble antibody scaffold - Koksal, Adem C. (MAbs, 2019)
G-protein coupled receptors (GPCRs) constitute major drug targets due to their involvement in critical biological functions and pathophysiological disorders. The leading challenge in their structural and functional characterization has been the need for a lipid environment to accommodate their hydrophobic cores. Here, we report an antibody scaffold mimetic (ASM) platform where we have recapitulated the extracellular functional domains of the GPCR, C-X-C chemokine receptor 4 (CXCR4) on a soluble antibody framework. The engineered ASM molecule can accommodate the N-terminal loop and all three extracellular loops of CXCR4. These extracellular features are important players in ligand recruitment and interaction for allostery and signal transduction. Our study shows that ASM(CXCR4) can be recognized by the anti-CXCR4 antibodies, MEDI3185, 2B11, and 12G5, and that ASM(CXCR4) can bind the HIV-1 glycoprotein ligand gp120, and the natural chemokine ligand SDF-1α. Further, we show that ASM(CXCR4) can competitively inhibit the SDF-1α signaling pathway, and be used as an immunogen to generate CXCR4-specific antibodies. This platform will be useful in the study of GPCR biology in a soluble receptor context for evaluating its extracellular ligand interactions.